Herbert: Design and Realization of a Full-Sized Anthropometrically Correct Humanoid Robot - Pierce, Brennand; Cheng, Gordon (Frontiers in Robotics and AI, 2015)
In this paper we present the development of a new full-sized anthropometrically correct humanoid robot Herbert. Herbert has 33 DOFs: 1) 29 active DOFs (2 × 4 in the legs, 2 × 7 in the arms, 4 in the waist and 3 in the head); 2) 4 passive DOFs (2 × 2 in the ankles). We present the objectives of the design and the development of our system, the hardware (mechanical, electronics) as well as the supporting software architecture that encompasses the realisation of the complete humanoid system. Several key elements, that have to be taken into account in our approach to keep the costs low while ensuring high-performance, will be presented. In realising Herbert we applied a modular design for the overall mechanical structure. Two core mechanical module types make up the main structural elements of Herbert: 1) small compact mechanical drive modules; and 2) compliant mechanical drive modules. The electronic system of Herbert, which is based on two different types of motor control boards and an FPGA module with a central controller, is discussed. The software architecture is based on ROS with a number of sub nodes used for the controller. All these supporting components have been important in the development of the complete system. Finally, we present results showing our robot’s performances: demonstrating the behaviour of the compliant modules, the ability of tracking a desired position/velocity as well as a simple torque controller. We also evaluate our custom communication system. Additionally, we demonstrate Herbert balancing and squatting to show its performance. Moreover, we also show the simplicity of the higher level supporting software framework in realising new behaviours. All in all, we show that our system is compact and able to achieve comparable human performances and has human proportions while being low cost.